An Analysis of Implicature and Speech Acts on Scarlett Whitening Advertisement: Study of Critical Discourse Analysis’s Sara Mills - Tessa Marlina; Aceng Ruhendi Saifullah (International Journal of Science and Applied Science: Conference Series, 2022)
The aims of this study are to describe the usage of implicature and kinds of speech acts used by Scarlett Whitening’s advertisement on Instagram captions and advertisement video on the Instagram official account Scarlett Whitening. Critical Discourse Analysis theory by Sara Mills will be the grand theory in this study. The implicature theory by Grice and Speech act theory by Searle will be conducted in this study. A descriptive qualitative method will be used in this study. The data in this study are kinds of words, phrases, and or sentences that contain implicature meaning from Scarlett Whitening’s advertisement in the form of an Instagram caption or speech from star ambassador, Korean actor Song Joong Ki in a video of Scarlett Whitening’s advertisement. The result shows that there is the usage of implicature and illocutionary speech acts in Scarlett Whitening’s advertisement.